Prevalence and pattern of perceived intelligibility changes in Parkinson's disease. Issue 11 (30th March 2007) - Miller, Nick; Allcock, Liesl; Jones, Diana; Noble, Emma; Hildreth, Anthony J; Burn, David J
Abstract : Background: Changes to spoken communication are inevitable in Parkinson's disease (PD). It remains unclear what consequences changes have for intelligibility of speech. Aims: To establish the prevalence of impaired speech intelligibility in people with PD and the relationship of intelligibility decline to indicators of disease progression. Methods: 125 speakers with PD and age matched unaffected controls completed a diagnostic intelligibility test and described how to carry out a common daily activity in an "off drug" state. Listeners unfamiliar with dysarthric speech evaluated responses. Results: 69.6% (n = 87) of people with PD fell below the control mean of unaffected speakers (n = 40), 51.2% (n = 64) by more than −1 SD below. 48% (n = 60) were perceived as worse than the lowest unaffected speaker for how disordered speech sounded. 38% (n = 47) placed speech changes among their top four concerns regarding their PD. Intelligibility level did not correlate significantly with age or disease duration and only weakly with stage and severity of PD. There were no significant differences between participants with tremor dominant versus postural instability/gait disorder motor phenotypes of PD. Conclusions: Speech intelligibility is significantly reduced in PD; it can be among the main concerns of people with PD, but it is not dependent on disease severity, duration or motor phenotype. Patients' own perceptions of the extent of change do not necessarily reflect objective measures.